"A critical study to find out the factors determining the preferences of consumers in selecting the telecommunication service provider" - Ms. Nikisha Kukreja, Dr. Parag Ajagaonkar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study intends to find the important factors that are considered while choosing a service provider. The consumers are asked why they have chosen a particular service provider and which factor was important to them while choosing a service provider. This study intends to explore the factors that are important by using exploratory factor analysis. Apart from that the study intends to find if there is any significant difference is the age group of a respondent and his buying preference. It further tries to find if there is any difference between prepaid and postpaid users and the importance given to factors while buying service provider.